Filtering Inequality: Screening and Knowledge in Senegal’s Topography of Hepatitis B Care - Tousignant, Noemi (Frontiers in Pharmacology, 2021)
Only a fraction of the estimated tenth or so of Senegalese who are chronically infected with hepatitis B virus (HBV) have been diagnosed. Of these, few have been assessed for their risk of progressing to potentially fatal liver disease (indicating need for treatment) and fewer still are taking antiviral drugs. A massive gap between those needing and getting treatment is widely acknowledged among experts. But given that HBV and its biomedical treatment options are largely invisible in bodies, health data, care practices, public messaging or mass media, how can we observe, ethnographically, the effects of constraints on and inequalities in treatment? What are the stakes of access to drugs, when this access is not being sought out, claimed or enacted? This article tackles these questions by examining how HBV is being enacted in Senegal, but not necessarily in relation to antiviral treatment. I first describe the emergence, over the past decade and a half, of an exclusionary topography of HBV diagnosis and treatment. I introduce the notion of “filtration” to describe the effects of this topography on the formation of potential “subjects of access.” The diagnostic therapies and expertise required to determine need for treatment are expensive, urban and largely privatised. Moreover, knowledge about HBV and its possibilities of care circulates in narrow and sparsely distributed channels. Only a tiny minority of persons are effectively “filtered into” care, while issues of access remain largely outside of public debate. I then move onto small-scale efforts, led by rural primary health workers and community associations, to raise awareness of, and expand screening for HBV. Those driving information and screening either do not know that effective drugs exist or locate these beyond the reach of most of their audiences or patients. Why then do they do it? I examine the logics and effects of their work to identify the forms of inclusion, care, efficacy and explanation these open up. At the same time, I seek to discern the indirect effects of unequal access to knowledge and resources in the ambivalence, uncertainties and contradictions that pervade these efforts to inform, diagnose and advise.